“AMPHIBIOUS RESILIENT HOUSE” – A USM INNOVATION FOR FLOOD DISASTERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 17 February 2016 – The School of Housing, Building and Planning (HBP) has put the Universiti Sains Malaysia (USM) name in the limelight recently with the winning entries of its students in different categories in the Autodesk Malaysia Design Competition (AMDC), organised together between Autodesk, the Ministry of Education Malaysia and Prestariang.